Protection and shelf-life extension of mango by a volatile compound, 3-methylpentanoicacid from endophytic bacterium, Bacillus safensis (Journal of Bangladesh Academy of Sciences, 2026)
Postharvest decay caused by Colletotrichum gloeosporioides (anthracnose) and Lasiodiplodia theobromae (stem-end rot) accounts for significant economic losses in global mango (Mangifera indica L.) value chains. While synthetic fungicides remain the primary control measure, escalating concerns regarding chemical residues and environmental toxicity necessitate the development of bio-based alternatives. This study identified and characterized the potent antifungal efficacy of 3-methylpentanoic acid (3- MP), a volatile organic compound (VOC) derived from the endophyte Bacillus safensis. In vitro assays demonstrated that 3-MP exerts dosedependent inhibition on critical fungal life stages, including mycelial expansion, conidial germination, and appressorium formation. Complete inhibition was achieved at concentrations as low as 200 μM for C. gloeosporioides and 300 μM for L. theobromae. In vivo application significantly suppressed disease severity, while storage trials revealed that 3- MP treatments (specifically at 100 μM) simultaneously delayed fruit ripening and minimized physiological weight loss. As a "Generally Recognized as Safe" (GRAS) compound, 3-MP represents a dual-action breakthrough: it serves as both a high-efficacy bio-fumigant and a physiological preservative. These findings provide a sustainable framework for replacing synthetic agrochemicals with microbial-derived volatiles, offering a scalable solution for the long-term preservation of tropical fruits.J. Bangladesh Acad. Sci. 50(2); 169–180: June 2026